Patient Information System and Doctor Competence in Increasing Satisfaction and Loyalty to Primary Level Health Service - Nur Choirul Afif; Lusi Suwandari (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
The establishment of Puskesmas (Community Health Centers) aims to make it possible for communities to get quality services that are affordable for all levels of society. The things that are necessary to be improved in the services of Puskesmas are the quality and access. This study aimed at predicting the factors influencing satisfaction and loyalty of BPJS patients of the primary level health facility. This research was an explanatory study aiming at determining whether there is an influence of management information system and doctor competence on patient satisfaction and patient loyalty. The results showed that the management information system (SIM) of the patients had a positive and significant influence on the BPJS patients’ satisfaction; doctor competence had a positive and significant influence on BPJS patients’ satisfaction; the management information system (SIM) of the patients had a positive and significant influence on the BPJS patients’ loyalty to the primary level health facility in Banjarnegara; doctor competence had a positive and significant influence on the BPJS patients’ loyalty, and patient satisfaction had a positive and significant effect on the BPJS patients’ loyalty to the primary level health facility in Banjarnegara.